Increasing energy and lysine in diets for growing-finishing pigs in hot environmental conditions: Consequences on performance, digestibility, slurry composition, and gas emission - Cerisuelo, Alba; Torres, Antonio G.; Lainez, Manuel; Moset, Verónica (2017)
The influence of dietary nutrient concentration on growth performance, manure composition, and gas emission was studied in pigs in hot environmental conditions. A total of 64 intact males and 64 females [(Landrace x Large White) x Pietrain] weighing 63.1 +/- 9.7 kg were divided into 2 dietary treatments: high (HD: 14.39 MJ of DE/kg and 1.11% Lys) and low (LD: 13.97 MJ of DE/kg and 1.01% Lys) in energy and Lys contents. Pigs were allocated to 32 split-sex pens with 4 pigs/pen and 16 pens/treatment. Average productive performance was recorded for 41 d (phase 1). After phase 1, 12 females of 103.3 +/- 3.15 kg (6 per treatment) were selected and housed individually, and feces and slurry were collected during 3 and 4 consecutive days, respectively, to calculate nutrient digestibility and measure gas emissions (phase 2). For gas emission measurements, slurry was pooled by treatment and stored for 76 d. Initial composition of slurry and pH were analyzed. Maximum and minimum temperatures registered in the barn throughout the growing period were 35.1 and 18.1 degrees C, respectively. Animals fed the HD diet grew more efficiently than pigs fed the LD diet (G:F, 0.43 vs. 0.40; SEM = 0.01; P < 0.05). Fat digestibility was greater in HD compared with LD pigs (88.0 vs. 84.9%; SEM = 0.9; P < 0.05). Slurry from pigs fed the LD diet showed greater DM, OM, total N, and VFA contents than slurry from pigs fed the HD diet. Cumulative NH3, CO2, and especially CH4 emissions were greater in the HD slurry compared with the LD slurry (192 vs. 210 g of NH3/m(3); 2,712 vs. 3,210 g of CO2/m(3); 1,502 vs. 2,647 mL of CH4/kg of OM). Increasing feed density in the present study led to a more efficient growth, a decreased nutrient concentration in the slurry, and a greater gas emission.